Manajemen Kurikulum Merdeka pada Sekolah Penggerak untuk Membentuk Profil Pelajar Pancasila di SMP Hang Tuah 6 Excellent Juanda Sidoarjo - Kusumawardani, Maharani Gita; Riyanto, Yatim; Purbaningrum, Endang; Nursalim, Mochamad; Khamidi, Amrozi (LP. Ma'arif Janggan Magetan, 2024)
This research aims to examine in depth the management of the independent curriculum in planning, organizing, implementing and evaluating schools related to the independent curriculum at sekolah penggerak to form the profile of Pancasila students at SMP Hang Tuah 6 Excellent Juanda. In order to achieve the research objectives, researchers used descriptive qualitative methods with a qualitative approach. The data collection techniques used by researchers were observation, interviews and documentation studies. The informants in this research were the school supervisor, principal, head of curriculum, teachers, students and guardians of students. The data analysis technique that researchers use is Miles and Huberman's data analysis technique which consists of four stages, namely data collection, data condensation, data presentation, and drawing conclusions. The results of this research show that (1) curriculum planning involves all parties through coordination meetings, monitoring by school supervisors and socialization of the program to parents of students. (2) the organization and implementation of the curriculum is carried out using the independent and shared curriculum with a focus on students through intracurricular activities, projects to strengthen the Pancasila student profile and extracurriculars. (3) curriculum evaluation is carried out involving school principals, school supervisors and teachers as facilitators. Evaluation is carried out once every three months in a comprehensive manner, both from implementation in the field and activity documents. Good synergy between schools, school supervisors, students and parents ensures that the goal of the independent curriculum is achieved, namely Pancasila student profile at SMP Hang Tuah 6 Excellent Juanda..